Study of various treatment modalities of caesarean scar pregnancy - Meghani, Prachi C.; Shah, Sapna R.; Vyas, Rupa C.; Parikh, Purvi M.; Chudasama, Tanmay J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Caesarean scar pregnancy (CSP) can be defined as the implantation of the gestational sac within the scar of a previous caesarean surgery. Incidence of CSP is 1 in 1800 pregnancies. Methods: It is a retrospective study based on clinical diagnosis and management of CSP of women who presented to the obstetrics and gynaecology department SVP hospital from January 2008 to August 2021. Total number of cases of CSP were 28. Incidence, gestational age, ultrasound findings, serum β-human chorionic gonadotropin (β-hCG) levels, flow profiles of color Doppler, and different methods of treatment were recorded. Diagnosis was confirmed by ultrasound. Results: In this study, all 28 cases of CSP considered were offered definitive management. In present study 5 cases (17.88%) showed torrential haemorrhage during dilatation and evacuation (D and E) which was treated by various methods like 1 (3.57%) Foley’s tamponade, 1 (3.57%) uterine artery embolization (UAE) and 3 (10.71%) hysterectomy. Hysterotomy was performed in 13 cases (46.42%) and (7.69%) of heterotrophic CSP (HCSP). One case (3.84%) of CSP presented at 26 weeks of gestation with haemorrhagic shock, underwent obstetric hysterectomy. Conclusions: There is a rise in the incidence of CSP because of increase in the global rate of caesarean sections and early transvaginal USG in pregnancy. Transvaginal sonography is the best diagnostic tool. Medical management can be offered when diagnosis is made at gestational age of <7 weeks. Whereas, surgical modalities have shown better results at >7 weeks of gestational age. Surgical management has an advantage of shorter follow up.